Analysis of the Influence of Investment, Premium Income, and Tabarru' Funds on Sharia Insurance Company Profits - Marwini Marwini; Munita Indah Lestari (At-Taqaddum, 2022)
This study aims to determine investment, premium income, and tabarru funds on profits of sharia life insurance companies in Indonesia. This study tested the hypothesis which stated that there was an effect of investment, premium income, and tabarru funds on profits. This data collection technique uses a purposive sampling technique with certain criteria. The population in this study were 24 sharia life insurance companies registered with the Financial Services Authority and the sample in this study were 6 sharia life insurance companies. Data analysis technique using multiple linear regression analysis. The research results showbased on the results of the regression test and t test investment has a positive and significant effect on insurance company profits. The tcount value is positive, meaning that the higher the investment, the higher the profit earned by the sharia life insurance company.Based on the results of the regression test and the t test, premium income has a positive and significant effect on insurance company profits. The tcount value is positive, meaning that the higher the premium income, the higher the profit earned by the sharia life insurance company.Based on the results of the regression test and t test, tabarru funds have a negative and significant effect on insurance company profits. The tcount value is negative, meaning that the higher the Tabarru fund, the lower the profit earned by the sharia life insurance company.